Membangun Keterampilan Berpikir: Potensi Guru Sejarah dalam Mempromosikan Literasi Kritis - Soma Surya Persada; Suryo Ediyono (Universitas Sebelas Maret, 2022)
The learning strategy applied by the history teacher basically affects the process and learning outcomes of students. Moreover, in the 21st century, various challenges arise so that the concept of 21st century education is needed to face these challenges. One of the efforts that history teachers can do in facing the challenges of 21st century education is to promote critical literacy. This article is a theoretical study written using the literature study method. The purpose of writing this article is to try to embody the two discussions. First, provision of critical literacy for prospective history teachers. Second, the strategy of history teachers in promoting critical literacy to students. Based on the results of the study of literature, it can be concluded that history teachers basically have the potential to promote critical literacy to students through the concept of historical thinking skills and controversial historical discourses. Considering that, in the education process at the tertiary level, prospective history teachers are very familiar with critical literacy so that they have the opportunity to transmit the implementation of critical literacy to students in secondary schools.